Evaluasi Unit Filtrasi IPAM Ngagel II Surabaya - Siti Kayyisa Nakhwa Endjani; Okik Hendriyanto Cahyonugroho (Faculty of Engineering, Universitas Serambi Mekkah, 2024)
IPAM Ngagel II Surabaya is one of the drinking water treatment plants managed by PDAM Surya Sembada Kota Surabaya, which was established in 1959 with a production capacity of 1000L/second. At IPAM Ngagel II, there are several treatment units consisting of intake, pre-sedimentation, accelerator, filtration and disinfection. The aim of this research is to evaluate the filtration unit as an optimisation effort to increase production capacity. The research was carried out by analysing the filtration performance to see the efficiency of removing turbidity and organic matter. The existing condition of the filtration unit was then compared with standard filtration unit design criteria. Water samples were taken in the morning for 20 days by testing the quality of the raw water and the effluent at the pre-sedimentation, accelerator and filtration treatment units. Based on the analysis results, the turbidity removal efficiency is more than 70% on average, while the organic matter removal efficiency is less than 20% on average. The way to optimise the filtration unit is not to change the condition of the existing unit, as the quality of the produced water still meets the standards, but it is necessary to check the height of the filter media and to replace single media with double media.